2014
DOI: 10.1186/s12884-014-0381-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in newborn care and newborn resuscitation following a quality improvement program at scale: results from a before and after study in Tanzania

Abstract: BackgroundEvery year, more than a million of the world’s newborns die on their first day of life; as many as two-thirds of these deaths could be saved with essential care at birth and the early newborn period. Simple interventions to improve the quality of essential newborn care in health facilities – for example, improving steps to help newborns breathe at birth – have demonstrated up to 47% reduction in newborn mortality in health facilities in Tanzania. We conducted an evaluation of the effects of a large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 15 publications
5
53
0
Order By: Relevance
“…This is consistent with previously published studies [12, 14]. In interviews, mentors suggested that knowledge of EBPs increased with training.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previously published studies [12, 14]. In interviews, mentors suggested that knowledge of EBPs increased with training.…”
Section: Discussionsupporting
confidence: 92%
“…Essential newborn care combines all gestures (resuscitation, hypothermia prevention, cord care, eye care, vitamin K1 administration, early initiation of breastfeeding and instructions for the first bath) were given to a newborn at birth to optimize his/her chance for survival [5] [6]. In Tanzania, an evaluation had revealed poor health professionals on ENC [7]. It led to massive training that resulted in a 47% reduction in neonatal mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, an evaluation had revealed poor health professionals on ENC [7]. It led to massive training that resulted in a 47% reduction in neonatal mortality [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality improvement approaches have been widely used with some success, such as in Tanzania, where performance in newborn care improved, but newborn resuscitation performance remained unchanged [31]. …”
Section: Human Resources For Mnch and Progress Towards Mdgs 4 And 5: Whmentioning
confidence: 99%